1989
DOI: 10.1093/nar/17.24.10367
|View full text |Cite
|
Sign up to set email alerts
|

A cDNA fragment of hepatitis C virus isolated from an implicated donor of post-transfusion non-A, non-B hepatitis in Japan

Abstract: Recently, a cDNA from the hepatitis C virus (HCV) RNA genome has been isolated in the USA from a chronically infected chimpanzee. In order to isolate HCV cDNA derived from human material, RNA was extracted from plasma of a Japanese blood donor implicated in post-transfusion non-A, non-B hepatitis and HCV cDNA was synthesized and amplified by the PCR method using HCV-specific oligonucleotide primers. The cDNA fragment, 583 nucleotides long, showed 79.8% homology at the nucleotide level and 92.2% homology at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 158 publications
(80 citation statements)
references
References 7 publications
3
76
0
1
Order By: Relevance
“…HCV cDNA fragments were obtained from the blood by RT-PCR. 20,21 Blood collected 6 months later was injected into chimpanzees and was infectious. The infectivity was 10 5.5 chimpanzee infectious doses/mL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…HCV cDNA fragments were obtained from the blood by RT-PCR. 20,21 Blood collected 6 months later was injected into chimpanzees and was infectious. The infectivity was 10 5.5 chimpanzee infectious doses/mL.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is impossible to assess the authenticity of the cDNA clones of HCV at the moment. However, the complete cDNA clone of HCV constructed in this study is believed to originate from infectious HCV clones for the following reasons: 1) the blood sample from the donor was infectious to both chimpanzees and humans 20,22 ; 2) from the sample, we isolated 12 overlapping clones covering the entire region of HCV that were major clones in each region, and their overlapping sequences were almost identical to the adjacent clones; and 3) the virus clones with sequences in HVR identical to those of the complete cDNA clone were detected in both recipient and chimpanzee after infection. Recently, Kolykhalov et al showed that in vitro synthesized full-length HCV RNA derived from the consensus cDNA clone was infectious to a chimpanzee after direct injection into the liver.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An aliquot of cDNA reaction solution (5 pl) was directly amplified by polymerase chain reaction (PCR) with a pair of primers 464 S (5'-GGCTATACCGGCGACTTCGA-3') and 526 A (5'-GACATGCATGTC-ATGATGTA-3'), encompassing the 623 base pairs (bp) (18). Amplification was done in a 100-pl reaction volume and on a DNA Thermal Cycler (Perkin Elmer Cetus, Norwalk, CN) for 5 min at 94 C, 1 min at 50 C and 1 min at 72 C for 10 min.…”
Section: Methodsmentioning
confidence: 99%